An Analysis On Students’ Difficulties in Changing Active to Passive in Writing For Tenth Grade at SMAN 21 - Rindu Kaya Sinambela; Yessy Octavianna; Nurhayati Sitorus (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah - 1, 2025)
Based on the results of observations made by researcher at SMA Negeri 21 Medan, researcher found several mistakes made by students in changing active sentences into passive, such as